The city in slang : New York life and popular speech - Allen, Irving L., 1931-2002 (Oxford University Press, 1993)
Irving Lewis Allen provides an insightful history of the rise of New York as a metropolis and the accompanying slang that surrounded it. Anecdotal and at times analytical, this book is both a lexicon of slang and a history of recent casual language.